1990
DOI: 10.1002/pd.1970100506
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal villus sampling in early second trimester: A safe sampling method for women of advanced age

Abstract: Transabdominal chorionic villus sampling (TA-CVS) was performed in 707 viable singleton pregnancies to exclude chromosomal abnormalities. Maternal age ranged between 36 and 49 years (mean 37.9 years); gestational age varied between 10.2 and 18.3 weeks (mean 13.3 weeks). In 639 women (90.4 per cent), a sufficient amount of chorionic tissue (greater than or equal to 10 mg) was obtained after one needle insertion; in 66 women (9.3 per cent) two insertions were needed. An abnormal chromosome pattern was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The number of sampling device insertions, one or two, did not influence the pregnancy outcome either in the transabdominal (3·2 per cent vs. 3·2 per cent) or in the transcervical (4·6 per cent vs. 5·29 per cent) cases. This is consistent with the findings of other investigators, who in addition observed that more than two insertions were associated with a higher loss rate (Hogge et al, 1986;Rhoads et al, 1989;Jahoda et al, 1990;Williams et al, 1992). This substantiates our protocol of limiting to two the number of device insertions in a single sampling session.…”
Section: Discussionsupporting
confidence: 93%
“…The number of sampling device insertions, one or two, did not influence the pregnancy outcome either in the transabdominal (3·2 per cent vs. 3·2 per cent) or in the transcervical (4·6 per cent vs. 5·29 per cent) cases. This is consistent with the findings of other investigators, who in addition observed that more than two insertions were associated with a higher loss rate (Hogge et al, 1986;Rhoads et al, 1989;Jahoda et al, 1990;Williams et al, 1992). This substantiates our protocol of limiting to two the number of device insertions in a single sampling session.…”
Section: Discussionsupporting
confidence: 93%
“…Chorionic villus samples were obtained under continuous ultrasound guidance by transabdominal aspiration as described previously (Jahoda et al, 1990). At least 20 mg of villi are required for chromosomal analysis of both STC-and LTC-villi in those cases where the indication for prenatal diagnosis is cytogenetic only.…”
Section: Methodsmentioning
confidence: 99%
“…Five to 35 mg (mean 14 mg) of chorionic villi was sampled transabdominally at 11-14 weeks of gestation as described previously (Jahoda et al, 1990). Indications for prenatal diagnosis were advanced maternal age (_36 years) (n=20), risk of X-linked mental retardation, recurrence risk of Niemann Pick type A, and risk of X-linked adrenomyeloneuropathy (each n=1).…”
Section: Patients and Proceduresmentioning
confidence: 99%